Internet w pracy dziennikarza prasowego - Mikosz, Joanna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2009)
The article discusses Internet as a one of the main sources of information in a work of the press journalist. It presents also selected titles of the electronic press and shows the rules of the work in a virtual editorial office. The text tries to answer too, if Internet is a reliable source of information.